Higher Order Thinking Skills pada Soal Akm Literasi Membaca di SMK Pertanian Pekanbaru - Sartika, Sartika; Mukhlis, Muhammad (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
The aim of this study is to determine and explain Higher Order Thinking Skills (HOTS) in the AKM literacy reading questions for Grade X in the even semester at SMK Negeri Pertanian Pekanbaru in 2021/2022. This is done to assess whether the characteristics of the questions align with the requirements. The research adopts a qualitative approach using content analysis as the method. Data collection techniques employed in this study include documentation, note-taking, writing, and drawing conclusions. The data collected is analyzed using content analysis techniques, involving identification, classification, analysis, and interpretation. The findings of this study reveal that the cognitive level in the AKM literacy reading questions consists of only two levels, namely understanding (C2) and analyzing (C4). Understanding (C2), classified as Lower Order Thinking Skills (LOTS), accounts for 68% of the questions, while analyzing (C4), classified as Higher Order Thinking Skills (HOTS), accounts for only 32%. Based on these calculations, the AKM literacy reading questions at SMK Negeri Pertanian Pekanbaru are still predominantly classified as LOTS, with a percentage of 68%.